Lifestyle Overview Of Hypertension Sufferers: Systematic Review - Regina Marintan Sinaga; Idris Adewale Ahmed (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Introduction: The increase in the number of hypertension sufferers can be caused by an unhealthy lifestyle. The number of hypertension cases in Indonesia is 63,309,620 people. Lifestyle factors that can be changed include diet, physical activity, smoking habits, and prolonged stress. Hypertension has a negative impact on cardiovascular, brain, kidney, and eye disorders. The purpose of this study was to determine the lifestyle of hypertension sufferers. Material and Methods: This study used a systematic literature review method. Data sources came from Google Scholar, Garuda Portal and Willey from 2015-2025. Article searches were based on the keywords lifestyle and hypertension. The review method was a literature selection based on preferred reporting items for systematic reviews and meta-analyses (PRISMA). The population in this study were hypertension sufferers with a minimum sample of 40 respondents. Inclusion criteria with journal content themes were lifestyle, diet, physical activity, smoking habits, and stress in hypertension sufferers. The maximum publication period of the journal was 10 years (2015-2025), and the languages used were Indonesian and English. The subjects were hypertension sufferers. The journal content consists of original research articles (not research reviews) in full text, with a cross-sectional design Results: Based on the results of the research from 5 articles analyzed, it is known that the lifestyle description of hypertension sufferers includes eating patterns, poor physical activity, experiencing stress, and not having a smoking habit. Conclusion: A good lifestyle for hypertension sufferers is one way to control the patient's blood pressure. Suggestions for nurses to implement hypertension management education interventions as a promotive and preventive effort for hypertension sufferers.